Read & Write (Me) QR Code In Reading And Writing Module - Ramamurthy, Lena; Shafien, Syakirah; Mohd Nawi, Noor Syamimie; Nik Azim, Nik Ahmad Farhan (2019)
Quick Response (QR) Code is no doubt a powerful tool that can be used to access the additonal and interactive resources provided by the instructors from time to time. What makes Read and Write (ME) QR code in Reading and Writing Module so extraordinary is its fruitful, authentic and interactive resources (immersive video and audio, kahoot, wiki, powerpoint slides, extended practices, official page, etc.) that learners, not only can be used in the class, but also outside of the class, especially during their self-learning tme (SLT). The tools needed are rather simple, just a smartphone, wifi and the module itself. Then, this hassle-free module is ready to be accessed at anytime and anywhere.